Epidemiology of Coronavirus Disease (COVID-19) in Nigeria - JO Bamidele; OJ Daniel (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
In late December 2019, there was an outbreak of a new Coronavirus infection in Wuhan, Hubei Province, China, which caused acute respiratory syndrome of unknown aetiology. The World Health Organization (WHO) named the virus Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV2) or COVID-19 and declared the infection a pandemic on the 11th of March 2020. The first case of COVID-19 in Nigeria was reported on the 27th of February 2020 and since then the numbers of confirmed cases has been on the increase, at least in Nigeria. With no vaccine or cure in sight, only public health measures that include personal protective measures, physical distancing, environmental and travel-related measures have been recommended to mitigate and contain the spread of the disease. There is need to make testing for COVID-19 widely available so that the true burden of the infection will be described. This step should assist policy makers in making evidence-based decisions in the prevention and control of the disease.